Training System - Bravo Bermeo, Cesar (Revista Universidad de Guayaquil, 2001)
Alexis de Tocqueville, author of Democracy in America, said that every book, and within every book, every part and every chapter, should always convey a single idea from which everything else can be deduced.Reading Miguel A. Zabalza's book University Education: The Setting and Its Protagonists allows us to identify that main idea, education, which is present and mentioned or inferred repeatedly in each of the five chapters that make up the book: The University, a specific and specialized setting for education; Organizational structures of university institutions; University faculty; University teacher training; University students.
Keywords: university education; training; educational institutions